New source-to-sink approach in an arctic catchment based on hyperspectral core-logging (Lake Linné, Svalbard). (1st January 2019) - Van Exem, Antonin; Debret, Maxime; Copard, Yoann; Verpoorter, Charles; De Wet, Gregory; Lecoq, Nicolas; Sorrel, Philippe; Werner, Alan; Roof, Steven; Laignel, Benoit; Retelle, Michael
Highlights: Hyperspectral core logging is a rapid and non-destructive technique in palaeolimnology. The technique is able to track lacustrine sediment sources. Environmental changes in the catchment-to-lake sedimentation and spatial sources are identified. This new method enables the fingerprinting of sedimentary sources with and/or without field samples. Data calibration allows reconstructing total organic carbon concentrations on several cores, at an unprecedented resolution.